The study on perceptions of the voters in N.12 Karambunai, Sepanggar / Arona Fiona Clement and Ramadia Karismah Mamang - Clement, Arona Fiona; Mamang, Ramadia Karismah (2014)
Election is an organized process in which people choose a person, to a position of public importance such as presidency or a group of people to represent them in national or state assemblies (S.S Islam & A.R. Moten). This process involves the act of selecting someone or something, the exercise of deliberate choice and casting votes to select the winner of a position. Basically, there are several functions of elections. The first one, elections are the means to reduce governments accountable to the governed. It means that, during the elections, the right person will be chosen and they will guide which also become the direct affairs of the government. Secondly, elections are important because it provide legitimacy to the government and also expected to convince the outside world that the government has mass support.